Strategi Kampanye Zakat pada Akun Instagram @Dompetdhuafaorg - Rahmi Hubbaka Ghayati; Lathifa Prima Ghanistyana; Neneng Widya Nengsih; Eka Septika; Hajar Azhari (MUKASI: Jurnal Ilmu Komunikasi, 2025)
The zakat campaign strategy implemented by the Instagram account @dompetdhuafaorg shows the effective use of social media as a means of disaster education and dissemination of philanthropic information to the public. Dompet Dhuafa utilizes the power of visual content such as images and videos in various post formats to convey information that raises awareness, especially to the upper class, so that they are encouraged to pay zakat and give alms. Through an emotional visual and narrative approach, this institution builds an emotional connection with followers, thereby increasing engagement and empathy for the conditions of people in need. In addition to conveying an invitation to donate through zakat, infak, and sedekah, this account is also a means of disaster mitigation education that can be widely accessed anytime and anywhere. This expands Dompet Dhuafa's role as a philanthropic institution that not only distributes funds, but also builds public awareness and preparedness for disasters. This strategy has proven successful in increasing public trust in Dompet Dhuafa, strengthening the institution's image as a professional and transparent entity. Thus, Instagram is not only a communication medium, but also transforms into an effective educational and fundraising platform.  This digital campaign is a real example of how the use of social media can significantly expand the reach and social impact of philanthropic institutions in today's digital era.